Effect of immediate and delayed cold water immersion after a high intensity exercise session on subsequent run performance - Brophy-Williams, N.; Landers, G.; Wallman, K. (Journal of Sports Science & Medicine, 2011)
The purpose of the study was to determine the effects of cold water immersion (CWI) performed immediately or 3 h after a high intensity interval exercise session (HIIS) on next-day exercise performance. Eight male athletes performed three HIIS at 90%VO2max velocity followed by either a passive recovery (CON), CWI performed immediately post-exercise (CWI(0)) or CWI performed 3 h post-exercise (CWI(3)). Recovery trials were performed in a counter balanced manner. Participants then returned 24 h later and completed a muscle soreness and a totally quality recovery perception (TQRP) questionnaire, which was then followed by the Yoyo Intermittent Recovery Test [level 1] (YRT). Venous blood samples were collected pre-HIIS and pre-YRT to determine C-Reactive Protein (CRP) levels. Significantly more shuttles were performed during the YRT following CWI(0) compared to the CON trial (p=0.017, ES = 0. 8), while differences between the CWI(3) and the CON trials approached significance (p = 0.058, ES = 0.5). Performance on the YRT between the CWI(0) and CWI(3) trials were similar (p = 0.147, ES = 0. 3). Qualitative analyses demonstrated a 98% and 92% likely beneficial effect of CWI(0) and CWI(3) on next day performance, compared to CON, respectively, while CWI(0) resulted in a 79% likely benefit when compared to CWI(3). CRP values were significantly lower pre-YRT, compared to baseline, following CWI(0) (p = 0.0.36) and CWI(3) (p = 0.045), but were similar for CON (p = 0.157). Muscle soreness scores were similar between trials (p = 1.10), while TQRP scores were significantly lower for CON compared to CWI(0) (p = 0.002 ) and CWI(3) (p = 0.024). Immediate CWI resulted in superior next-day YRT performance compared to CON, while delayed (3 h) CWI was also likely to be beneficial. Qualitative analyses suggested that CWI(0) resulted in better performance than CWI(3). These results are important for athletes who do not have immediate access to CWI following exercise.